TEXTURE MEASUREMENT BY NEUTRON DIFFRACTION FOR A1 NON STANDARD STEEL BARS - Aziz K. Jahja; Nurdin Effendi; M. Refai Muslich (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2011)
TEXTURE MEASUREMENT BY NEUTRON DIFFRACTION FOR A1 NON STANDARD STEEL BARS. Texture measurements are used to determine the orientation distribution of crystalline grains in a polycrystalline sample. A material is termed textured if the grains are aligned in a preferred orientation along certain lattice planes. The texture is usually introduced in the fabrication process (e.g. rolling of thin sheet metal, deposition, etc.) and affects the material properties by introducing structural anisotropy. The pole figure is the starting point of neutron texture analysis. Texture properties in an non-standard austenite Fe-Ni low carbon alloy were measured by the neutron diffraction method with the PD/Residual Stress Diffractometer DN3 apparatus in BATAN. In this paper, effects of hot rolling on the texture are studied using ODF plots generated by MAUD application code developed by Lutteroti. It was found that The ODF plots for the A1 as cast and 1200 °C hot rolled specimens show typical patterns for recrystallized and rolled cubic structure. The pole figures for this plate are consistent with Face Centered Cubic (FCC) rolling textures.